GAMBARAN PROSES ADMINISTRASI DALAM PENGELOLAAN OBAT DI INSTALASI FARMASI PUSKESMAS CAKRANEGARA - Ifayatul Ahyani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
The purpose of this study is to determine and provide an explanation of how the administrative process in managing drugs in the pharmaceutical installation of the Cakranegara Health Center is related to planning, procurement, receipt, storage, distribution, control, recording and reporting, withdrawal and destruction, monitoring and evaluation. The research method used is a descriptive method through questionnaires and interviews, because the researcher wants to know the description of the administrative process in managing drugs in the pharmaceutical installation at the Cakranegara Health Center. Management of drugs and disposable medical materials at the Cakranegara Health Center has been implemented in accordance with applicable standards and provisions, especially the Minister of Health Regulation No. 73 of 2016.